Pediatric Pulmonary Hypertension is Associated With Increased Circulating Levels of BMP 7 and CHIP - Edward C. Kirkpatrick; Stephanie Handler; Melodee Liegl; Amy Y. Pan; G. Ganesh Konduri; Todd M. Gudausky; Adeleye J. Afolayan (Pulmonary Circulation, 2025)
ABSTRACT Pulmonary arterial endothelial and smooth muscle cell homeostasis is regulated through the bone morphogenetic protein (BMP) and transforming growth factor beta (TGF‐β) receptor pathways. Pathway imbalance results in pulmonary hypertension (PH). Each pathway has ligands and modulators influencing this balance. How these pathways differ in pediatric PH patients is unknown. Ten PH and 20 control subjects (ages 2–17 years) were prospectively enrolled. Pulmonary artery serum BMP 2, 4, 6, 7, 9, 10, activin A, TGF‐β1, carboxyl terminus of Hsc70‐interating protein (CHIP), NT Pro BNP, and CRP were measured by ELISA. Analyses were made using the Fisher's exact test, the Mann–Whitney test, ROC analysis, and Pearson and Spearman correlations as appropriate. PH subjects were group 1 (four with simple shunts) or group 3 PH. Control subjects had shunts scheduled for catheter closure but no PH. Only BMP 7 and CHIP levels were statistically elevated in PH patients versus controls; (BMP 7 0.081(0.076–0.084) vs. 0.074(0.069–0.08) OD, p = 0.044), (CHIP 0.17(0.14–0.24) vs. 0.13(0.12–0.15) OD, p = 0.007) respectively. BMP 7 levels correlated with RV systolic pressure (0.431, p = 0.02) and pulmonary resistance (0.446, p = 0.013). CHIP correlated with mean pulmonary artery pressure (0.449, p = 0.013) and resistance ratios (Rp/Rs) (0.419, p = 0.02). BMP 7 OD of 0.077 had sensitivity/specificity of 80% and 70% for PH. CHIP OD of 0.136 had sensitivity/specificity of 90% and 65% for PH. BMP 7 and CHIP levels are heightened in pediatric PH patients which correlate with catheterization values. BMP 7 and CHIP could provide sensitive markers for PH to aid in diagnosis and disease monitoring.